Grapevine: An exercise in distributed computing - Birrell, Andrew; Levin, Roy; Needham, Roger M.; Schroeder, Mike (Communications of the ACM, 1982)
Grapevine is a multicomputer system on the Xerox research internet. It provides facilities for the delivery of digital messages such as computer mail; for naming people, machines, and services; for authenticating people and machines; and for locating services on the internet. This paper has two goals: to describe the system itself and to serve as a case study of a real application of distributed computing. Part I describes the set of services provided by Grapevine and how its data and function are divided among computers on the internet. Part II presents in more detail selected aspects of Grapevine that illustrate novel facilities or implementation techniques, or that provide insight into the structure of a distributed system. Part III summarizes the current state of the system and the lessons learned from it so far.